Pengaruh E-Service Quality dan E-Trust Terhadap Kepuasan Pelanggan Pada Pengguna Aplikasi PLN Mobile Kota Padang Panjang - Luthfiani, Fatma; Yuhefizar, Yuhefizar; Josephine Sudiman (Akuntansi dan Manajemen, 2024)
Technology has become an inseparable part of people's daily lives. The high use of cellphones and the internet in Indonesia has triggered companies to follow the wishes of the community by creating several applications that are used for the above activities. Several mobile applications already exist in Indonesia, one of which is for payments and purchases. One of the companies that provides mobile payment applications is the State Electricity Company (PLN), which is an Indonesian State-Owned Agency that operates in the electricity sector. In the final assignment with the title "The Influence of E-Service Quality and E-Trust on Customer Satisfaction for Users of the PLN Mobile Application in Padang Panjang City" the author compiled using a quantitative approach with descriptive statistical analysis techniques. This research aims to determine the effect of e-service quality on customer satisfaction of PLN Mobile application users in Padang Panjang City and to determine the influence of e-trust on customer satisfaction of PLN Mobile users in Padang Panjang City. The number of respondents was 68 PLN Padang Panjang City customers who were chosen randomly. The results of this research show that e-service quality and e-trust have a significant effect on customer satisfaction for users of the PLN Mobile application in Padang Panjang City.